2023
DOI: 10.1002/ecs2.4495
|View full text |Cite
|
Sign up to set email alerts
|

Niche specialization and community niche space increase with species richness in filter‐feeder assemblages

Abstract: Ecological theory posits that higher species richness should be associated with greater exploitation of resources and niche packing resulting from either increasing species niche overlap or specialization of species' niches. Research evaluating niche theory in animals tends to focus on organisms among functional feeding guilds, while resource partitioning might be more critical within functional groups. Freshwater mussels (Family: Unionidae) are a diverse and imperiled group of animals that are ideal models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
7
1
Order By: Relevance
“…Factors that were expected to increase the specialization of species were similarly found to generally increase the proportion of forest species in an area. The third factor tested was the total species richness of an area, and we found that this had consistently strong effects on the proportion of forest species, supporting the ‘niche packing’ hypothesis that species are required to specialize in more specific niches to maintain a stable community with high species richness (Macarthur, 1965; Sánchez González et al., 2023). This is further corroborated by the weak effect of total species richness in our model including all taxa, indicating that niche‐packing is working at an intra‐taxa level, in which species are more likely to be competing for shared resources.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Factors that were expected to increase the specialization of species were similarly found to generally increase the proportion of forest species in an area. The third factor tested was the total species richness of an area, and we found that this had consistently strong effects on the proportion of forest species, supporting the ‘niche packing’ hypothesis that species are required to specialize in more specific niches to maintain a stable community with high species richness (Macarthur, 1965; Sánchez González et al., 2023). This is further corroborated by the weak effect of total species richness in our model including all taxa, indicating that niche‐packing is working at an intra‐taxa level, in which species are more likely to be competing for shared resources.…”
Section: Discussionsupporting
confidence: 66%
“…Niche packing As species richness increases, niches must be further partitioned and therefore the proportion of specialist species increases (Macarthur, 1965;Sánchez González et al, 2023). If these species inhabit forested areas, then we would expect a higher proportion of forest specialist species in areas with higher species richness…”
Section: Narrow Physiological Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…For example, many Lampsiline species exhibited negative trends of genetic diversity in species-rich communities (Figure 4b). Although we were not able to identify any mussel traits linked to such patterns, prior work from the same sites studied here suggests that Lampsilis ornata populations contract their trophic niche space in species-rich communities (Sánchez González et al, 2023). Some discrepancies were also observed for AGDCs, including two species from the Tribe Lampsilini (most notably L. ovata and O. reflexa) that exhibited negative genetic diversity-density trends.…”
Section: Discussioncontrasting
confidence: 60%
“…Mussel communities are often patchily distributed and the amount of viable habitat within a given watershed area or reach may be limited (Strayer, 2008), and some mussel species may be in direct competition with others (Ferreira-Rodríguez et al, 2018;Modesto et al, 2021). Areas with greater mussel species richness may not have larger population sizes for each species, as competition for resources within spatially constrained communities may lead to reduced trophic niche usage and smaller populations in some species (Sánchez González et al, 2023;Scheele et al, 2017). Mixed support for a relationship between species richness and genetic diversity expected under the SGDC hypothesis (Vellend, 2005), and lack of a significant relationship between genetic diversity and cumulative multispecies density of all mussels, provide some support for the idea that processes leading to the accumulation of species at the community level may not always be linked to the processes favouring large populations and genetic diversity of individual species at particular sites (McCain, 2021;McCain et al, 2018).…”
Section: Discussionmentioning
confidence: 99%